(untitled) (Global Journal of Science Frontier Research, 2015)
The article examines the impact of eastern galega on some indicators of composition and properties of podzolic soils in the conditions of the middle taiga of Western Siberia. It is shown that in the early stages of development of eastern galega is depleted soil organic matter and some deterioration of its properties, but in the future restoration of soil trend indicators. Especially intensively these processes are at sowing galega east under cover of peas and in the application of microbiological preparation Baikal-EM1.